2020
DOI: 10.1007/s00330-020-07082-3
|View full text |Cite
|
Sign up to set email alerts
|

Tibiopedal and distal femoral retrograde vascular access for challenging chronic total occlusions: predictors for technical success, and complication rates in a large single-center cohort

Abstract: Objective To evaluate the safety and effectiveness of tibiopedal and distal femoral access for retrograde crossing of chronic total occlusion (CTO) in Rutherford stage III to VI peripheral arterial occlusive disease, and to determine factors that correlate with technical success. Material and methods One hundred seventy-one consecutive patients were included in this retrospective study. Rutherford stages were III, IV, and V/VI in 24%, 8%, and 67% of patients. Inclusion criteria were CTO at the superficial femo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…In our study, The technical success was achieved in 20 cases with percentage of (83.3%), and not achieved in 4 cases (16.7%) only, however technical success rate of crossing of 82% was similar to previously published data ranging from 75 to 100% as reported by [ 15 ],also, Andrej Schmidt, MD et al in his study reported the retrograde access success in 98.6 % [ 16 ], the procedure success rates were very high (>95%) as reported in the study of [ 17 ]. Hosam El-Sayed et al in his study reported that the technical success rate of 67% was low, compared with earlier studies.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our study, The technical success was achieved in 20 cases with percentage of (83.3%), and not achieved in 4 cases (16.7%) only, however technical success rate of crossing of 82% was similar to previously published data ranging from 75 to 100% as reported by [ 15 ],also, Andrej Schmidt, MD et al in his study reported the retrograde access success in 98.6 % [ 16 ], the procedure success rates were very high (>95%) as reported in the study of [ 17 ]. Hosam El-Sayed et al in his study reported that the technical success rate of 67% was low, compared with earlier studies.…”
Section: Discussionsupporting
confidence: 91%
“…As regard indications of procedure: In our study, half of the cases indicated for rest pain (50%) and other half for tissue loss (37.5% for ulcer, 12.5% for gangrene), Hosam El-Sayed et al, reported in his study 19% of cases indicated for claudications, 5% for rest pain, 76% “majority of cases” for tissue loss [ 13 ], DM, CAD and HTN were present with percentage (94%), as reported in the literature [ 12 ], also, Zoltan Ruzsa et al, reported in his study that 53% 0f cases indicated for gangrene (majority), 37% for ischemic rest pain, 16% for ulcer [ 15 ].…”
Section: Discussionmentioning
confidence: 84%